ANALISIS FAKTOR â FAKTOR YANG MEMPENGARUHI RETURN SAHAM (Kasus pada Perusahaan Manufaktur yang Go Public di BEI periode tahun 2005 - 2009) - Arista, Desy; Astohar, Mr (STIE Totalwin Semarang, 2012)
Problems in the study of some previous studies showed inconsistent results, this research was conducted to re-examine the influence of fundamental factors consisting of return on assets (ROA), debt to equity ratio (DER), earnings per share (EPS), and price to book value (PBV) together and partial effect on Stock Return manufacturing companies in Indonesia Stock Exchange in 2005-2009. The sample size used in this study was of 114 manufacturing companies went public on the Stock Exchange with the determination of the sample using purposive sampling. The type of data using secondary data using documentation. Return on assets (ROA) has no significant effect on stock return manufacturing companies listed on the Indonesia Stock Exchange. Debt to equity ratio (DER) has a significant influence on stock return manufacturing companies listed on the Indonesia Stock Exchange. Earning per Share (EPS) has no significant effect on stock return manufacturing companies listed on the Indonesia Stock Exchange. Price to book value (PBV) has a significant influence on stock return manufacturing companies listed on the Indonesia Stock Exchange. Taken together (simultaneously) return on assets, debt to equity ratio, earnings per share and price to book value has a significant influence on stock return manufacturing companies listed on the Indonesia Stock Exchange. Keywords: Return on Assets, Debt To Equity Ratio, Earning Per Share, Price To Book Value and Stock Return